Fluorescent Dye Assay for Detection of DNA in Recombinant Protein Products. (September 1997) - Bolger, R.; Lenoch, F.; Allen, E.; Meiklejohn, B.; Burke, T.
A homogeneous fluorescence-based DNA detection system has been developed to measure DNA in protein solutions. The technique relies on the increase in fluorescence of a dye molecule when it intercalates into double-stranded (ds) DNA. The increased fluorescence is a direct measurement of the amount of DNA in the sample. The analysis time required per sample is less than 5 min. The dye has absorbance and emission maxima at 485 and 530 nm, respectively. The assay is linear from 98 pg/mL to 200 ng/mL of DNA in buffers containing no proteins with typical relative standard deviation values of less than 2.4%. The assay performance was evaluated under various matrix conditions, including buffers, pH, ionic salts, detergents, denaturants and organic solvents. Each reagent was tested at several concentrations to determine how the slope and linearity ( r value) of the standard curve were affected. Even in the presence of matrix components and protein, the assay was able to quantitatively detect picogram to nanogram levels of DNA. The fluorescence can be removed by DNase treatment. This method is specific for dsDNA with RNA emitting less than 2% intensity of an equivalent mass of DNA.